Multiband Superconductivity, Polarons, Jahn-Teller Polarons, Heterogeneity, and High-Temperature Superconductivity - Annette Bussmann-Holder; Hugo Keller (Condensed Matter)
Early on, oxides were ruled out from superconductivity, since they are typically large-band-gap insulators. Nevertheless, a rather small number of them were found to be superconducting, with transition temperatures up to 14 K and a remarkably low carrier density. This was the starting point of K. Alex Müller (KAM) becoming interested in superconductivity in oxides. Step by step, he advanced the research on oxides and finally discovered, together with J. Georg Bednorz, high-temperature superconductivity (HTSC) in the perovskite-type compound Ba-La-Cu-O. Even though he was inspired by specific and clear ideas in his search, he added new impact in the understanding of HTSC for many years after receipt of the Nobel prize for this discovery.